Gene Therapy for the Treatment of Parkinson's Disease: The Nature of the Biologics Expands the Future Indications - Massimo S. Fiandaca; Howard J. Federoff; Krystof S. Bankiewicz (MDPI AG, 2012)
The pharmaceutical industry's development of therapeutic medications for the treatment of Parkinson's disease (PD) endures, as a result of the continuing need for better agents, and the increased clinical demand due to the aging population. Each new drug offers advantages and disadvantages to patients when compared to other medical offerings or surgical options. Deep brain stimulation (DBS) has become a standard surgical remedy for the effective treatment of select patients with PD, for whom most drug regimens have failed or become refractory. Similar to DBS as a surgical option, gene therapy for the treatment of PD is evolving as a future option. In the four different PD gene therapy approaches that have reached clinical trials investigators have documented an excellent safety profile associated with the stereotactic delivery, viral vectors and doses utilized, and transgenes expressed. In this article, we review the clinically relevant gene therapy strategies for the treatment of PD, concentrating on the published preclinical and clinical results, and the likely mechanisms involved. Based on these presentations, we advance an analysis of how the nature of the gene therapy used may eventually expand the scope and utility for the management of PD.